Trisomy 18: A single‐center evaluation of management trends and experience with aggressive obstetric or neonatal intervention. Issue 4 (5th January 2016) - Subramaniam, Akila; Jacobs, Adam P.; Tang, Ying; Neely, Cherry; Philips, Joseph B.; Biggio, Joseph R.; Robin, Nathaniel H.; Edwards, Rodney K.
Abstract : We conducted a retrospective cohort study including all prenatal and postnatal diagnoses of trisomy 18 (T18) from 2004 to 2014 at a single tertiary referral center in the southern United States to evaluate the natural history and perinatal outcomes associated with T18 over the past decade. We analyzed pregnancy outcome, mode of delivery, and for live‐births, the number and types of neonatal interventions, and characterized interventions as aggressive or non‐aggressive. Survival analyses were conducted based on mode of delivery and aggressive compared to non‐aggressive interventions. A total of 167 cases of T18 were identified, 150 with available records. There were 141 (94.0%) with full T18; the remainder had mosaicism (1.3%), a translocation (0.7%), or an isochromosome 18 (4.0%). Most diagnoses were prenatal (73.3%, n = 110). Of the 150 patients, there were 54 live births: 21 (38.9%) delivered vaginally, 32 (59.3%) delivered by cesarean, and mode of delivery could not be ascertained for one. Median duration of survival was 12 days (interquartile range 3–90 days). Over time, there were no changes toward increased intervention (obstetric or neonatal). For the 49 neonates who received some intervention, there was no significant difference in survival time between neonates receiving aggressive (n = 36, median survival 24 days, interquartile range 6–247) and non‐aggressive (n = 13, median survival 30 days, interquartile range 8–148) intervention ( P  = 0.90). There was similarly no difference in neonatal survival based on mode of delivery ( P  = 0.79). Survival of infants with T18 is not improved with aggressive obstetric or neonatal care. © 2016 Wiley Periodicals, Inc.